Disorder and Transport Properties of In3SbTe2 – an X‐ray, Neutron and Electron Diffraction Study1. Issue 14 (15th August 2013) - Schröder, Thorsten; Rosenthal, Tobias; Grott, Sebastian; Stiewe, Christian; de Boor, Johannes; Oeckler, Oliver
Abstract Quenched metastable In3SbTe2 was investigated by X‐ray and neutron powder diffraction as well as by single‐crystal X‐ray diffraction. The average structure corresponds to the rocksalt type, the anion position being occupied by antimony and tellurium. Neutron data indicate no antisite disorder of indium and antimony. The compound is a high‐temperature phase that can be quenched to yield a metastable compound at ambient temperature which, upon heating, decomposes at ca. 320 °C into InSb and InTe. Diffuse scattering in reconstructed X‐ray and selected area electron diffraction patterns indicates local distortions of the crystal structure due to static atom displacement along <100> from the average positions, caused by the different size of the anions, but no superstructure. The electrical conductivity of In3SbTe2 is 3.2 × 104 S·cm–1 at 25 °C, the temperature characteristics correspond to metallic behavior. Consequently, the thermal conductivity is also rather high. The decomposition into InSb and InTe reduces the electrical conductivity by a factor of 3 in heterogeneous microstructures.